Etiology, Pathogenesis and Outcomes of Patients Treated at the Burn Center of N.V. Sklifosovsky Research Institute for Emergency Medicine - A. V. Sachkov; T. G. Spiridonova; E. A. Zhirkova; P. A. Brygin; K. S. Smirnov (Неотложная медицинская помощь)
Background We identified patients treated at our Burn Center over a 14-year period.Material and methods The following data were studied: the annual and total number of patients, the number of patients admitted to the Intensive Care Unit (ICU) and the Burn Unit (BU), gender and age of the patients, the epidemiology of burn injury, percentage of total body surface area (TBSA) burned, percentage of inhalation injury, percentage of full thickness burns, mortality.Results It was revealed that the annual number of patients averaged 730 (692; 747). The proportion of those hospitalized to the ICU was 35–49%, and 51–65% to the BU. These figures did not differ significantly (all p>0.05; Fisher exact test [FET]). The male to female ratio was 2.3-1.6:1. The age of the patients increased from 44 (31; 59) to 48 (33; 62) years (p=0.003; M–W test). The percentage of the etiological factors changed: flame burns accounted for 60% of cases in 2006 and 34% of cases in 2019 (p<0.001; FET). The number of patients with scalds increased from 18% in 2006 to 33% in 2019 (p=0.023; FET). The proportion of patients with inhalation injury without burns did not exceed 15% for the entire study period. Median burn area among all hospitalized decreased by almost twice from 2006 to 2019: total area from 12% to 7% TBSA (p<0.001; M–W test); superficial, from 10 to 6% TBSA (p<0.001; M–W); deep burns, from 9 to 3% TBSA (p<0.001; M–W). In patients in the ICU, the median of the total burned area was 20–25% TBSA, the area of superficial burns prevailed without a statistically significant difference between 2006 and 2019. (p=0.285; M–W test). The median area of deep burns gradually decreased by more than twice: from 15% TBSA in 2006 to 7% TBSA in 2019 (p<0.001; M–W test). For the period from 2006 to 2019 overall mortality in the burn center decreased from 16.7% to 7.4% due to a 2.4-fold decrease of mortality from 16.3% to 6.9% in the ICU (p<0.001; FET). In the BU, for the entire period it was 0.4-1.6%. In 2019, the highest mortality of 27% was observed in combined burns and inhalation injury (InI) followed by InI without burns (13.6%), and then came electrical injury (11.8%).Conclusion For 14 years, mortality has decreased by more than twice. The highest number of deaths was observed among patients with skin burns and InI, InI without burns and electrical injury. Annual number of admissions in ICU and BU, gender ratio remained steady. The median area of total burns decreased by 2-3 times, the median area of deep burns in patients in the ICU decreased by 2 times. The median age of burn patients increased by 4 years and began to refer to the middle age group according to the WHO classification.